2020
DOI: 10.3390/insects11060344
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rosmarinus officinalis Essential Oil Fumigation on Biochemical, Behavioral, and Physiological Parameters of Callosobruchus maculatus

Abstract: This study explores the influence of rosemary, Rosmarinus officinalis (L.) essential oil (EO) on the biochemical (acetylcholinesterase, catalase, and glutathione S-transferase), physiological (oxygen consumption), and behavioral (open field test, repellency) parameters of an important stored product insect: cowpea weevil, Callosobruchus maculatus (F.). R. officinalis EO exhibited effective insecticidal action against C. maculatus even at relatively low concentrations. LC50 = 15.69 μL/L air, and was highly repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 37 publications
2
22
0
1
Order By: Relevance
“…Some EOs contain majority compounds resembling those obtained in the B. cinerea EOs used in the present study. Using the fumigation technique, the EOs of Rosmarinus officinalis L., composed mainly of α-pinene (22.64%), camphor (21.84%), 1,8-cineole (21.53%), and camphene (9.18%), show an insecticidal effect against C. maculatus with an LC 50 = 15.69 µL/L air [ 43 ]. In a recent study [ 44 ], it was reported that the EOs of Salvia officinalis , containing α-thuyone (24.27%), camphor (18.10%), 1–8 cineol (14.38%), and β thujone (7.38%) as major components, were toxic against C. maculatus , while batches treated with 16 μL/L of EOs air resulted in 33.5% of eggs hatched, while 24% evolved into larvae and 19.5% was the number of emergences.…”
Section: Resultsmentioning
confidence: 99%
“…Some EOs contain majority compounds resembling those obtained in the B. cinerea EOs used in the present study. Using the fumigation technique, the EOs of Rosmarinus officinalis L., composed mainly of α-pinene (22.64%), camphor (21.84%), 1,8-cineole (21.53%), and camphene (9.18%), show an insecticidal effect against C. maculatus with an LC 50 = 15.69 µL/L air [ 43 ]. In a recent study [ 44 ], it was reported that the EOs of Salvia officinalis , containing α-thuyone (24.27%), camphor (18.10%), 1–8 cineol (14.38%), and β thujone (7.38%) as major components, were toxic against C. maculatus , while batches treated with 16 μL/L of EOs air resulted in 33.5% of eggs hatched, while 24% evolved into larvae and 19.5% was the number of emergences.…”
Section: Resultsmentioning
confidence: 99%
“…Different plant EOs including A. annua, Artemisia sieberi Besser, L. angustifolia, Melia azedarach L., Pteridium aquillinum L., and T. vulgaris have previously been studied for their deterrent, toxic, and developmental inhibitory activities against X. luteola at the larval stage. The EOs derived from A. annua, A. sieberi [1,36], T. vulgaris, L. angustifolia [34], and R. officinallis [37] have shown repellence, toxicity, biochemical, behavioral, and physiological properties against X. luteola. However, the present study offers the first evidence of the ovicidal effect of A. annua, L. angustifolia, O. vulgare, R. officinalis, S. hortensis, and T. vulgaris EOs against X. luteola eggs.…”
Section: Discussionmentioning
confidence: 99%
“…and lepidopteran pests like Cadra cautella (Walker) (Lee et al 2002;Isikber et al 2006). Terpenes and monoterpenes of R. officinalis affect the central system of insects by inhibiting acetylcholinesterase enzymes (Krzyzowski et al 2020).…”
Section: Discussionmentioning
confidence: 99%